Calculus: Early Transcendentals 8th Edition

Published by Cengage Learning
ISBN 10: 1285741552
ISBN 13: 978-1-28574-155-0

Chapter 9 - Section 9.3 - Separable Equations - 9.3 Exercises: 10

Answer

$z = -ln(e^t + C)$

Work Step by Step

$dz/dt + e^{t+z} = 0$ This can be rewritten as: $dz/dt = -e^{t+z}$ $dz/dt = -e^te^z$ Now let's separate z and t: $e^{-z} dz = -e^t dt$ Now let's integrate both sides: $\int e^{-z} dz = \int -e^t dt$ $-e^{-z} = -e^t + C$ To isolate z, we can add ln() on both sides: $ln(-e^{-z}) = ln(-e^t + C)$ $-z = ln(-e^t + C)$ $ z = -ln(-e^t + C)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.